Cofilin-induced unidirectional cooperative conformational changes in actin filaments revealed by high-speed atomic force microscopy - Ngo, Kien Xuan (eLife, 2015)
High-speed atomic force microscopy was employed to observe structural changes in actin filaments induced by cofilin binding. Consistent with previous electron and fluorescence microscopic studies, cofilin formed clusters along actin filaments, where the filaments were 2-nm thicker and the helical pitch was ∼25% shorter, compared to control filaments. Interestingly, the shortened helical pitch was propagated to the neighboring bare zone on the pointed-end side of the cluster, while the pitch on the barbed-end side was similar to the control. Thus, cofilin clusters induce distinctively asymmetric conformational changes in filaments. Consistent with the idea that cofilin favors actin structures with a shorter helical pitch, cofilin clusters grew unidirectionally toward the pointed-end of the filament. Severing was often observed near the boundaries between bare zones and clusters, but not necessarily at the boundaries. DOI: http://dx.doi.org/10.7554/eLife.04806.001